(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
The relict endemic of flora of the mountain Crimea Silene jailensis is known from four places in upper belt of the Crimea Mountains. Small quantity of the endemic (500 plants) is explained by the taxon genesis in upper belt, which was destroyed. The seasonal rhythm of plants was studied in natural conditions and in conditions ex situ in low belt in subtopic climate.